(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
This article presents opinions on improving and analyzing regulatory and legal acts concerning the legal framework and system for increasing energy efficiency and introducing renewable energy sources. It also analyzes the most important issues related to environmental law theory and the further development of the legal framework system for increasing energy efficiency and introducing renewable energy sources. The legal foundations for improving energy efficiency and introducing renewable energy sources are examined from the perspective of the origin of the right to use them within the framework of scientific research, as well as the national and international significance of energy law within the system of natural resources. Improving energy efficiency and introducing renewable energy sources are implemented in certain forms and methods. Legal relations connected with the concept of ecological and legal formation of energy security, the content of the norms aimed at their regulation, the essence and problems of their practical application, the management system in the field of national and international energy consumption, as well as the protection of the concept of ecological and legal formation of energy security and the powers of management bodies are implemented in the following cases.